CREATIVE CASE ELSIE DE Wolfe and FRANK LLOYD WRIGHT ON CENTURY 20 - Sunarmi Sunarmi (Pendhapa, 2012)
This paper titled Creative Case Elsie de Wolfe and Frank Lloyd Wright 20th Century. This paper is the result of literature study to explore the question of how the role of the creative process Elsie de Wolfe and Frank Lloyd Wright, in the field of interior design in the 20th century and how the environmental factors that influence the creative process Elsie de Wolfe and Frank Lloyd Wright. The approach used to borrow theories of Sigmund Freud, about the social influences on personality characteristics.Discussion of the results show, in the 20th century two trends emerged in the case of the creative design process. The first, conducted by Elsie de Wolfe leads to a form of conservation is a growing trend since ancient times, who faithfully follow and build on the traditions of the past history and tradition only slightly developed. This conservative tendency leads to the improvement of the visual style of the surface treatment and decoration, colors and textures, fixtures and accessories. The second, conducted by Frank Lloyd Wright tendency which aims to encourage innovation and new discoveries, which leads to the front and the futuristic new. This approach can be said to be more radical. This approach looked at all aspects of interior design as a potential for experimentation and progress. This approach is directed to examine the forms of space, system-structural systems and construction of space, patterns of functional activity space, the use of new materials, new manufacturing processes, and other aspects of interior design that have a direct appeal, ie, walls, ceilings , flooring, furniture, and other objects. The final goal of this trend is the incorporation of all the above elements in order to achieve overall consistency of the design as a result of the new design. The case related to the creative, creative way someone can be summed up basically not escape the influence of inner experience and empirical experience. At the level of the inner experience of it driven by the demands of the environment when it should behave and act while living in an environment that will form the habit of a person who in the end became a personality. The attitude of a person or individual social representation called kepribadaian formed as influenced by social climate or social structures in the environment. The personality characteristics influenced the work of many designers or artists is basically a naturally occurring process. This suggests that social action is created on the basis of a personâ€™s personality or psychological processes that formed him based on the interpretation of other interpretations.Â Keywords: Creative, Personality, Character Work